Análise da distribuição da riqueza gerada por meio da Demonstração do Valor Adicionado - Antonio Marcelino, José (2021)
Using one of the components of the Social Balance Sheet, we selected the Statement of Added Value (DVA), which aims to demonstrate the formation of wealth. This research analyzes the contributions to all economic agents, and its objective is to analyze and demonstrate the formation of the wealth generated from the two companies listed in B3 (Brazil, Stock Exchange, Balcão), Sabesp, which has mixed economy, that is, it brings together private and public capital, and Iguá, which has a private economy. Both are from the water and sanitation sector, and the research was conducted from 2013 to 2018. It is necessary to consider the great importance of them for society, because they are of public utility, and also to present the wealth that was distributed to society compared to that distributed by privateagents. The theoretical framework was structured in Social Responsibility, Social Balance Sheet, Value Added Demonstration and a brief summary of the companies analyzed. The research methodology was documentary analysis, case study, descriptive, qualitative and quantitative analysis.